2002
DOI: 10.1093/chemse/27.5.475
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Physiology of the Serotonin-immunoreactive Putative Antennal Lobe Feedback Neuron in the Male Silkmoth Bombyx mori

Abstract: In the male silkmoth Bombyx mori, olfactory information is relayed from olfactory receptor neurons in the antennae to the antennal lobe, and then to a variety of protocerebral neuropils. Currently, very little is known about neuromodulators that may affect the dynamics of this olfactory neural network. Immunocytochemical studies have revealed the presence of a serotonin-immunoreactive (SI) neuron that, in several insect species, is thought to provide feedback to the antennal lobe. To date, no studies have reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 22 publications
4
52
1
Order By: Relevance
“…Taken together, these data suggest the possibility of non-synaptic release of serotonin. Serotonin could potentially diffuse throughout a glomerulus and bind to receptors in outer regions of the glomerulus where the SI neuron does not branch (Kent et al, 1987;Sun et al, 1993;Hill et al, 2002). Thus, serotonin released from the SI neuron could potentially bind to receptors on the sensory terminals (located in the outer regions of glomeruli).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these data suggest the possibility of non-synaptic release of serotonin. Serotonin could potentially diffuse throughout a glomerulus and bind to receptors in outer regions of the glomerulus where the SI neuron does not branch (Kent et al, 1987;Sun et al, 1993;Hill et al, 2002). Thus, serotonin released from the SI neuron could potentially bind to receptors on the sensory terminals (located in the outer regions of glomeruli).…”
Section: Discussionmentioning
confidence: 99%
“…A pair of unique serotonin-immunoreactive (SI) neurons that innervate both ALs has been identified in many insects (Sch眉rmann and Klemm, 1984;Kent et al, 1987;Rehder et al, 1987;Homberg and Hildebrand, 1989;Breidbach, 1990;Salecker and Distler, 1990;Sun et al, 1993;Hill et al, 2002). The B. mori SI neuron innervates every glomerulus in the contralateral AL, fires longduration spontaneous action potentials and responds to mechanosensory stimuli to the antennae (Hill et al, 2002).…”
mentioning
confidence: 99%
“…Furthermore, Hill et al (2002) showed that this SI neuron spikes spontaneously and responds to mechanosensory stimuli to the antennae. Due to the fact that, in M. sexta, its branchings in the AL contain mostly output synapses (Sun et al, 1993), the SI neuron may be involved in a feedback system from the protocerebrum to the AL.…”
Section: Serotonin Modulates Sensitivity To Bombykolmentioning
confidence: 99%
“…In moths, serotonin may be released in the ALs by a single pair of serotonin-immunoreactive (SI) neurons with branches in every glomerulus of the AL as well as in higher order neuropil regions of the brain (Kent et al, 1987;Hill et al, 2002). Furthermore, Hill et al (2002) showed that this SI neuron spikes spontaneously and responds to mechanosensory stimuli to the antennae.…”
Section: Serotonin Modulates Sensitivity To Bombykolmentioning
confidence: 99%
See 1 more Smart Citation